Multi‐stage superelastic variable stiffness pendulum isolation system for seismic response control of bridges under near‐fault earthquakes. Issue 12 (19th October 2022) - Zheng, Wenzhi; Tan, Ping; Liu, Yanhui; Wang, Hao; Chen, Huating
Abstract: To improve the resilient capability of bridges, a novel multi‐stage superelastic variable stiffness pendulum isolator (SVSPI) is developed by incorporating superelastic shape memory alloy (SMA) with the multi‐stage variable stiffness pendulum isolator (VSPI), which featured with the favorable adaptability under service conditions and near‐fault excitations. Based on OpenSees platform, the numerical model for novel multi‐stage superelastic variable stiffness pendulum isolator is created. A fractional factor based design method is suggested for parameter optimization of the multi‐stage superelastic variable stiffness pendulum isolator. The example bridges with the novel isolators are designed to conduct the seismic mitigation investigation under near‐fault earthquakes. The effectiveness of the novel superelastic multi‐stage variable stiffness pendulum isolator and suggested design method is further discussed by case study. Results show that the novel multi‐stage superelastic variable stiffness pendulum isolator designed by the proposed fractional factor based design method can perform the dual control of the isolator residual displacement, girder displacement, and base forces in piers for bridges. The effectiveness of the multi‐stage superelastic variable stiffness pendulum isolator with the optimal parameters is demonstrated by case study. The technical achievements can provide reliable basis for structural resilience enhancement and potential structural applications.